Spinal Intramedullary Schwannoma of the Conus - Jeyaselva Senthilkumar TP; Sekar Chinnamuthu (Indian Journal of Neurosurgery)
Schwannomas are one of the most common primary spinal tumors representing 30% of all intraspinal lesions. Intramedullary schwannomas constitutes 0.3% of all intraspinal tumors and approximately 1% of spinal cord schwannomas. Majority of the tumors are seen in the cervical (58%), followed by thoracic (32%) and lumbar (10%) regions. Very few are reported at the level of conus medullaris. The important radiologic features of intramedullary schwannoma are predominant extramedullary component, intramedullary spinal tumor with a thickened and enhancing spinal nerve root, absent syrinx, enhancing well with contrast, and sharp margins. The aim of surgery in intramedullary spinal schwannomas is total removal whenever possible. Diagnosing intramedullary schwannoma preoperatively needs high index of suspicion. We are reporting the 10th case of intramedullary schwannoma in the conus region.